Zirconium in the Nuclear Industry 1984
DOI: 10.1520/stp34476s
|View full text |Cite
|
Sign up to set email alerts
|

In-Reactor Creep of Zr-2.5Nb

Abstract: The anisotropy of irradiation creep of Zr-2.5Nb alloy tubes at 570 K has been investigated using creep of helical springs and stress relaxation of twisted rods and bent beams. These tests measure creep rate directly since strains associated with irradiation growth are absent. Creep rates from these tests and from results on creep of pressurized tubes reported in the literature can be correlated through consideration of the crystallographic texture, slip systems, and dislocation density of the Zr-2.5Nb tubing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, cold work also affects other 2 metallurgical parameters: grain shape and texture, all of which can affect creep rate. The results from relaxation tests [27] at 570 K showed that the irradiation creep rate of cold-worked Zr-2.5Nb is only slightly dependent on dislocation density as measured by X-ray diffraction. A dependency of ρ 0.2 is normally suggested [26].…”
Section: Effect Of Dislocation Densitymentioning
confidence: 98%
See 1 more Smart Citation
“…However, cold work also affects other 2 metallurgical parameters: grain shape and texture, all of which can affect creep rate. The results from relaxation tests [27] at 570 K showed that the irradiation creep rate of cold-worked Zr-2.5Nb is only slightly dependent on dislocation density as measured by X-ray diffraction. A dependency of ρ 0.2 is normally suggested [26].…”
Section: Effect Of Dislocation Densitymentioning
confidence: 98%
“…All the mechanisms are related to the creation of point defects during irradiation and their interaction with the fabrication-induced microstructure and with subsequently evolved microstructure with irradiation. The 2 most prominent mechanisms are stress-induced preferential absorption of point defects at dislocations and climb followed by glide of dislocation [27]. The application of a diffusional mass transport model based on interstitial/vacancy diffusion towards grain boundary sinks appears to be a strong support on the effect of grain size/ shape [25].…”
Section: Figurementioning
confidence: 98%
“…Isolating them as an independent variable is difficult due to the variety of thermo-mechanical processes that affect both size and shape of grains. For Zircaloy, Franklin et al [30] and Holt [102], report only small effects on creep, with grain shape (aspect ratio) having a stronger influence than the mean size. Kreyns and Burkhart [74] report larger relaxation creep rates in Zircaloy for fine grained, cold-worked and recrystallized microstructure than for larger grained hot-rolled microstructures, but the influence of fabrication variables was not clear.…”
Section: Influence Of Grain Size and Shapementioning
confidence: 99%
“…Lower-bound [8,9] and upper-bound [10] polycrystalline models were first used to predict anisotropic irradiation creep of zirconium alloys assuming dislocation creep as the strain-producing mechanism. However, the lower-bound model over-estimates the polycrystalline deformation rate and the total deformation strain due to the lack of constraint between grains; and the upper-bound model under-estimates the deformation rate and total deformation because of the full constraint applied by matrix [11].…”
Section: Polycrystalline Model-selfpolymentioning
confidence: 99%